2016
DOI: 10.1016/j.tecto.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Devonian–Permian sedimentary basins and paleogeography of the Eastern Russian Arctic: An overview

Abstract: The Arctic basins attract broad international interest because of the region's potentially significant undiscovered hydrocarbon resources. The Russian High Arctic is mostly represented by broad shelves, with a few wells drilled only in its western part (Kara and Barents shelves). This contribution provides an overview of the geological setting, stratigraphy, paleogeography, and tectono-sedimentary evolution of the middle-late Paleozoic basins of the Eastern Russian Arctic, including: Severnaya Zemlya, the New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 42 publications
(102 reference statements)
0
18
0
Order By: Relevance
“…Detrital zircon study of the upper Palaeozoic rocks revealed dominant Mesoproterozoic to middle Paleozoic detrital zircon populations with almost complete absence of Paleoproterozoic and Archean grains [31,120]. Therefore, this terrane is very unlikely to have been connected with the Siberian Craton in Palaeozoic.…”
Section: Arctic Alaska-chukotka Microcontinent (Aacm)mentioning
confidence: 96%
“…Detrital zircon study of the upper Palaeozoic rocks revealed dominant Mesoproterozoic to middle Paleozoic detrital zircon populations with almost complete absence of Paleoproterozoic and Archean grains [31,120]. Therefore, this terrane is very unlikely to have been connected with the Siberian Craton in Palaeozoic.…”
Section: Arctic Alaska-chukotka Microcontinent (Aacm)mentioning
confidence: 96%
“…74 ), and ( c ) simplified and generalized stratigraphic column of Permian sedimentary rocks of South Taimyr (modified from ref. 75 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stratigraphic column of Devonian-Permian rocks of study Area 1 (thickness and lithology are mainly based on our field data with age constrains mainly based on Kos'ko et al, 1985). deposits in the southern part of the island varies from 1 to 7.7 km, however this great thickness is likely to be an overestimation due to repetition of the stratigraphy by faulting and folding (Ershova et al, 2016b). The Frasnian deposits crop out in both study areas.…”
Section: Devonianmentioning
confidence: 90%